Study of multiple antennas with defected ground slot for low-band LTE application - Wai Loon Cheor; Azremi Abdullah Al-Hadi; Ping Jack Soh; Mohd Faizal Jamlos (Institute of Advanced Engineering and Science, 2019)
This study is focused on highly coupled multiple antennas with defected ground slot techniques. Two Printed Inverted-F Antenna (PIFA) are positioned at the top edge of chassis symmetrically. Both antennas are operating at low-band Long-Term Evolution (LTE) with center frequency, 829MHz. Rectangular defected ground slot is implemented to reduce the coupling effect between the antennas on the ground plane of the small chassis. Parameter study of the rectangular defected ground slot is studied with different width, W and length, L. Furthermore, the optimized dimensions of rectangular defected ground slot, W and L are simulated and presented. The optimized defected ground slot reduced the mutual coupling up to -4.5 dB. The envelope correlation coefficient (ECC) achieved less than 0.5. The ground plane of the multiple antenna structure has been further investigated by introducing another slot with a gap of 1mm between them. The achieved result is not significant in term of S-parameter and ECC compared to single defected ground slot.